SEPULUH UNSUR PENGOPTIMAL METODE DRIL DAN PENGUASAAN HAFALAN BAHASA MANDARIN KOMPREHENSIF - Yogi Bagus Adhimas; Muhammad Farid Ilhamuddin; Miftachul Amri (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
This study discusses the advantages and optimization of the drill method in the memorization process for mastery of Mandarin. The drill method that does not require additional media, and only relies on the five human senses is an advantage that deserves to be maximized. This study aims to offer ten elements that can encourage better results in the process of memorizing Mandarin with the drill method. By using qualitative research methods, elements, such as, relying on continuity, familiarizing with Mandarin language culture, determining the appropriate mindset for improving mastery of Mandarin memorization with the dril method, are a summary of the results in the elements offered and in the discussion will be presented with in-depth elaboration.